Pengaruh Pendekatan Open-ended Terhadap Kemampuan Berpikir Kreatif Matematis Peserta Didik. - Adi S Situmorang (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2022)
The purpose of this study was to determine the effect of the open-ended approach on the mathematical creative thinking skills of students in class VIII of SMP N 3 Raya. This type of research is a quasi-experimental study with the research population being all eighth grade students of SMP N 3 Raya T.A. 2022/2023. With the Simple Random Sampling technique, the research samples were obtained for the experimental class, namely class VIII-1 and class control class VIII-2, each class consisting of 30 students. From the results of calculating the post-test value of mathematical creative thinking skills using the Liliefors rule and the results of normality analysis using Kolmogorov-Smirnov for creative thinking skills for the experimental class and control class, it is stated that all data on creative thinking skills come from data that is normally distributed. From the table of Test of Homogeneity of Variances for the test of creative thinking ability, it also shows that the two data of creative thinking ability are homogeneous. From the results of the ANOVA calculation, the sig value is obtained. = 0.02 <0.05, which means that there is a difference in increasing critical thinking skills between the open-ended approach and the conventional approach of 4.591. From the t-test calculation, it was found that the significant value = 0.027 <0.05, which means that there is an effect of the open-ended approach on the creative thinking ability of students. From the interaction graph, it is clear that there is an interaction between the learning approach and the ability to think creatively, so it can be concluded that there is an effect of the open-ended learning approach on the creative thinking ability of students in class VIII SMP N 3 Raya.